(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In the article the features of creative freedom in implementing discourse Lesya Ukrainka´s dramatic poem «Autumn Tale». By revealing the specific content and expressions appointed discourse on the material character of the work, conflicts and collisions, symbols. Distinguishes different facets of creative style playwright associated with the discourse of freedom.